Chronic pain in Parkinson disease - A. Palamarchuk (Kazimierz Wielki University, 2020)
The study was aimed to assess the modern trends explaining pathogenesis of chronic pain amongst patients with PD. The information search in the open sources was conducted using databases OVID, PubMed and EMBASE, the depth of search was in time frame after 2010. Content analysis was provided for the most pertinent literature reviews and clinical trials. There were selected 12 sources amongst 89 primary found references. There were discussed the main domains of pathogenesis of chronic pain in Parkinson disease. The approaches to pain management in PD patients primarily depend on the underlying cause. The presence of chronic pain syndrome should be considered as a reason for assessing the adequacy of antiparkinsonian therapy